Provérbios no ensino de PBE: uma proposta de unidade didática - Costa, Ivy Jesus da (2010)
This study concerns a practice for teaching Brazilian language and culture specifically developed for a group of African students of the Programa Estudante Convênio- Graduação (PEC-G), enrolled in the Course of Portuguese for Foreigners offered by Universidade Federal Fluminense. Considering the importance of Oral Tradition in the cultural background of these students, we assumed that the teaching of PROVERBS could be a potentially interesting genre as a starting point for a teaching experiment of the target language and culture, which would blend nicely with the learners previous knowledge. Textbooks of Portuguese for Foreigners edited in Brazil do not present a satisfying approach of PROVERBS. And whenever they appear it is out of context. Our goal was to develop activities of oral and written comprehension and production based on contextual PROVERBS, so as to support our assumption. These activities, compiled as a didactic unit (presented here as Appendix A), were tested on a class of Congolese students. They have shown to be very useful as didactic material for teaching Brazilian language and culture to groups of PEC-G hosted every year by several Brazilian universities.